The long term effects of firearm injuries on special senses - Shrinivas Chavan; Rakesh Waghmare; Vinayak Kurle; Archana Sylendran (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Introduction: Special senses are group of sensory organs that help us to connect with external environment by various modes of elements like sound, sight, touch and smell. Any damage to these organs though may not be physically handicapping but can affect the quality of life of any individual. Bullet injuries to the head and neck region are life-threatening and demand a detailed clinical examination and meticulous operative management due to the complexity of craniofacial anatomy. Head and neck region also house sense organs, but most of the time their functions are not properly assessed during the primary care provided in firearm injuries. The main aim of this study was - To study the long term effects of firearm injuries on special senses. To study the impact of these injuries on facial visage causing impairment on quality of life. To set a standard protocol that can be applied in such injuries for a bedside evaluation of sense organs of victims. Materials and Methods: The following study was conducted by the Department of Otorhinolaryngology & Head and Neck Surgery, Department of Forensic Medicine and Department of Community Medicine, at Grant Government Medical College and Sir JJ Group of Hospitals. A retrospective study of 532 patients who were victims of various firearm injuries in isolated civil incidents and terrorist attacks in Mumbai between January 1990 to July 2018. Institutional ethical clearance was obtained prior to initiating the study. Data regarding the patients were obtained from hospital records. Results: The age group which was most affected was between 20- 40 years i.e.; the working population of the country. Most of the patients were of the male gender, nearly 70.3%. The sense organ to be affected the most in these incidents was ear(55.2%) ,followed by eyes(39.3%) . Facial scar caused a significant social impact on the quality of life among females. Conclusion: This study aims to set a standard protocol in the post-critical phase in firearm injuries; giving priority to functions of sense organs and facial visage to ensure a good quality of life in the post-trauma period.